Papillary carcinoma thyroid in pregnancy: a case report - Tyagi, Sonali; Singh, Maya; Sharma, Himani; Chaudhary, Rohit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Thyroid cancer is the fastest rising type of cancer seen among women. Being the second most common carcinoma in pregnancy, it is important to evaluate the physiological changes in pregnancy that may contribute towards development of this condition. Although most thyroid cancers recognized during pregnancy require surgical treatment, but when it needs to be operated on, is dependent on multiple factors along with patients’ choice. A 23-year-old primigravida with 6 weeks gestation presented with a midline neck swelling for 4 months. Small initially, it gradually started to increase in size. Radiological and fine needle aspiration cytology was suggestive of papillary carcinoma thyroid. Patient was taken up for surgery in second trimester under general anesthesia-total thyroidectomy with modified radical neck dissection. Till date, limited data is available on the effect of pregnancy on evolution of malignancy so as to prevent it at the right time. This report consolidates the etiology, guidelines and management of thyroid cancer in pregnancy.